Geographical distribution of Anopheles minimus species A and C in western Thailand - Ampornpan Kengluecha (2018)
Elucidating vector distribution based on an accurate species identification is important to understanding the nature of the species complex in order to achieve vector control. Morphologically, An. minimus s.l. is difficult to distinguish from both its species complex and its closely related species. A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique and a single multiplex-allele specific PCR developed for species identification were applied in this study in comparison with morphological identification. Both methods were used, combining with geographical information systems to determine the distribution of An. minimus species A and C. The investigation on the breeding habitats was performed in the malarious area of western Thailand. Anopheles larvae were collected from 36 bodies of water among five districts (Sangkhaburi, Thong Pha Phum, Si Sawat, Muang, and Sai Yok) of Kanchanaburi Province, Thailand. In this study, An. minimus A larvae were present in all study districts but the association differed when focusing on study sites within each district. Although there were many reports of An. minimus A in Ban Phu Rat and Ban Phu Toei villages in Sai Yok District, we did not find the breeding sites of species A in those two areas. An. minimus A and C were found in Ban Phu Ong Ka village in Sai Yok District. The breeding habitats of An. minimus C were present covering 30-40 km of distance in northern part of Sai Yok and this species was also found in the central and southern parts of Si Sawat District.